Comparison of inspiratory effort with three variable-flow nasal continuous positive airway pressure devices in preterm infants: a cross-over study. Issue 4 (15th January 2021) - Bordessoule, Alice; Moreira, Amelia; Felice Civitillo, Cristina; Combescure, Christophe; Polito, Angelo; Rimensberger, Peter C
Abstract : Objective: Patient's work of breathing may vary between different neonatal nasal continuous positive airway pressure (NCPAP) devices. Therefore, we aimed to compare the inspiratory effort of three variable-flow NCPAP delivery systems used in preterm infants. Design: Cross-over study. Patients/setting: From June 2015 to August 2016, 20 preterm infants weighing ≤2500 g requiring NCPAP for mild respiratory distress syndrome were enrolled. Interventions: Each patient was successively supported by three randomly assigned variable-flow NCPAP systems (MedinCNO, Infant Flow and Servo-i) for 20 min while maintaining the same continuous positive airway pressure level as the patient was on before the study period. Main outcome measures: Patients' inspiratory effort was estimated by calculating the sum of the difference between maximal inspiratory and baseline electrical activity of the diaphragm (∆EAdi) for 30 consecutive breaths, and after normalising this obtained value for the timing of the 30 breaths. Results: Physiological parameters (oxygen saturation measured by pulse oximetry, respiratory rate, heart beat, transcutaneous partial pressure CO2 ) and oxygen requirements remained identical between the three NCPAP systems. Although a wide variability in inspiratory effort could be observed, there were no statistically significant differences between the three systems for the sum of ∆EAdi for 30 breaths: CNO, 262 (±119) µV; IF, 352 (±262) µV; and SERVO-i, 286 (±126) µV, and the ∆EAdi reported on the timing of 30 breaths (sum ∆EAdi/s): CNO, 6.1 (±2.3) µV/s; IF, 7.9 (±4.9) µV/s; SERVO-i, 7.6 (±3.6) µV/s. Conclusion: In a neonatal population of preterm infants, inspiratory effort is comparable between the three tested modern variable-flow NCPAP devices.